Pengaruh Pendidikan, Pengalaman Kerja, dan Jam Kerja Terhadap Pendapatan Usaha di Sentra Industri Tahu Tropodo, Kecamatan Krian, Kabupaten Sidoarjo - Aditya Bagus Hendrawan; Muhammad Yasin (Student Research Journal, 2023)
There is a number of affecting issues about impact level income received by entrepreneurs in the Tofu Center Industry Tropodo like factor education, experience and also work times factor. Study this done for prove influence problem about business revenue and expected can useful for overcome problem happened. This Study formed from method quantitative with technique testing hypothesis done with use analysis multiple linear regression. Population and sample in this study are 31 entrepreneurs and also 31 labor in the Tofu Centers Industry, Tropodo, District Krian, Sidoarjo City. Test simultaneously (Test F) shows that education, experience and work times influential in a manner together and significant to business revenue in the Tofu Centers Industry Tropodo District Krian, Sidoarjo City. Test partial (t test) shows that variable education influential in a manner positive to business revenue. Temporary variable experience work influential in a manner positive to business revenue, and work times variable influential in a manner positive to business revenue. This Study show if education, experience and work times influential to business revenue in the Tofu Centers Industry Tropodo, District Krian, Sidoarjo City